Secondary battery, device, artificial graphite and preparation method
By using artificial graphite with appropriate volume average particle size and controlling its distribution in the negative electrode sheet, the problem of volume expansion during the secondary battery cycle is solved, and the battery life is extended and safety performance is improved.
Patent Information
- Application Number
- CN201980066376.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-12-03
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2039-12-03
AI Technical Summary
The secondary battery will expand in volume during circulation, resulting in an increase in internal stress, affecting the battery's service life and safety performance.
Artificial graphite with a volume average particle diameter Dv50 of 12μm to 22μm as the negative electrode active material, and when the compaction density of the negative electrode sheet is 1.6g/cm3 to 1.75g/cm3, the peak area and the crystal surface of the artificial graphite are controlled. The ratio of the peak area of the 110 crystal plane is within a specific range to reduce the direction selectivity during the lithium embedding process and reduce the cyclic expansion of the secondary battery.
It significantly reduces the cyclic expansion of the secondary battery, extends the cycle life of the battery and improves safety performance.
Smart Images

Figure CN113207314B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of secondary batteries, and specifically relates to a secondary battery, a device, artificial graphite and a preparation method. Background Art
[0002] Secondary batteries are widely used due to their outstanding features such as high energy density, no pollution and long service life.
[0003] However, secondary batteries will expand in volume during the cycle, which will increase the internal stress of the battery and affect the battery's service life and safety performance. For example, with the rapid popularization of new energy vehicles, the market has higher and higher requirements for the service life and safety performance of power secondary batteries. In order to enhance the market competitiveness of new energy vehicles, it is necessary to provide a new technology that can reduce the volume expansion of secondary batteries. Summary of the invention
[0004] The present application provides a secondary battery with low cycle expansion, a device including the secondary battery, artificial graphite capable of reducing the volume expansion of the secondary battery during the cycle process, and a preparation method thereof.
[0005] In order to achieve the above-mentioned object, the present application provides a secondary battery in a first aspect, which comprises a negative electrode plate, wherein the negative electrode plate comprises a negative electrode active material, wherein the negative electrode active material comprises artificial graphite, and the volume average particle size D of the artificial graphite is v 50 is 12 μm to 22 μm, and the artificial graphite satisfies: 12 ≤ D v 50×SSA≤25, where SSA is the specific surface area of the artificial graphite, in m 2 / g; the compaction density of the negative electrode sheet is 1.6g / cm 3 ~1.75g / cm 3 , the OI value of the negative electrode plate is ≤15, wherein the OI value of the negative electrode plate = C 004 / C 110 , C 004 is the peak area of the diffraction peak of the 004 crystal plane of the artificial graphite in the negative electrode plate, C 110 is the peak area of the diffraction peak of the artificial graphite 110 crystal plane in the negative electrode plate. The peak area of the diffraction peak can be obtained by X-ray diffraction spectrum testing.
[0006] In the secondary battery provided in the present application, the negative electrode active material includes artificial graphite, and when the compaction density of the negative electrode sheet is 1.6 g / cm 3 ~1.75g / cm 3When the ratio of the peak area of the 004 crystal plane to the peak area of the 110 crystal plane of the artificial graphite is within a specific range, the directional selectivity of the artificial graphite in the lithium insertion process is significantly reduced, thereby reducing the volume expansion of the negative electrode sheet and the secondary battery during the cycle. v 50 is appropriate, and D v 50 and the specific surface area SSA satisfy a specific relationship, thereby enabling the artificial graphite to have a higher surface stability, reducing the side reaction between it and the electrolyte, and reducing the gas production. Under the combined effect of the above conditions, the cycle expansion of the secondary battery is greatly reduced, thereby effectively improving the cycle life and safety performance of the secondary battery.
[0007] In any embodiment of the first aspect of the present application, the volume average particle size D of the artificial graphite is v 50 is 15μm~18μm.
[0008] In any embodiment of the first aspect of the present application, the artificial graphite satisfies: 15≤D v 50×SSA≤22; Optionally, the artificial graphite satisfies: 16≤D v 50×SSA≤21. When the volume average particle size Dv50 of artificial graphite is appropriate and a specific relationship is satisfied between its Dv50 and specific surface area SSA, it can have a higher surface stability, reduce the side reaction between it and the electrolyte, and reduce the gas production.
[0009] In any embodiment of the first aspect of the present application, the compaction density of the negative electrode plate is 1.6 g / cm 3 ~1.7g / cm 3 ; Optional: 1.62g / cm 3 ~1.68g / cm 3 The ratio of the peak area of the artificial graphite 004 crystal plane to the peak area of the 110 crystal plane is within a specific range, so that its directional selectivity in the lithium insertion process is significantly reduced, and the lithium insertion expansion can be dispersed in all directions, thereby reducing the volume expansion of the negative electrode sheet and the secondary battery during the cycle process.
[0010] In any embodiment of the first aspect of the present application, the OI value of the negative electrode plate is 8 to 12. The artificial graphite in the negative electrode plate can have a high bonding force with the negative electrode collector, thereby further reducing the cycle expansion of the plate and the battery.
[0011] In any embodiment of the first aspect of the present application, the volume particle size distribution D of the artificial graphite v 10≥6μm, optional 6.5μm≤D v10≤10.5μm. The active specific surface area of the artificial graphite is small, which can further reduce the side reaction energy in the secondary battery. It is also beneficial for the electrode to obtain a higher compaction density.
[0012] In any embodiment of the first aspect of the present application, the particle size span (D v 90-D v 10) / D v 50 is 1.1 to 1.8, and can be 1.2 to 1.5. The stacking performance between artificial graphites can be improved, and the negative electrode sheet using the artificial graphite has a proper porosity. At the same time, the artificial graphite can also have a proper active specific surface area, so that it has both high electrochemical reaction activity and high surface stability.
[0013] In any embodiment of the first aspect of the present application, the graphitization degree of the artificial graphite is 90% to 95%, and can be 92% to 94%. The graphitization degree of the artificial graphite within the above range can make it have a higher powder compaction density and gram capacity.
[0014] In any embodiment of the first aspect of the present application, the tap density of the artificial graphite is 0.85 g / cm 3 ~1.35g / cm 3 , optional 0.95g / cm 3 ~1.15g / cm 3 .
[0015] In any embodiment of the first aspect of the present application, the powder compaction density of the artificial graphite under a pressure of 2000 kg is 1.65 g / cm 3 ~1.85g / cm 3 , optional 1.68g / cm 3 ~1.83g / cm 3 Artificial graphite has a higher powder compaction density under a pressure of 2000kg. The negative electrode sheet using the artificial graphite can have a higher compaction density, thereby making the battery have a higher energy density.
[0016] In any embodiment of the first aspect of the present application, the number particle size distribution D of the artificial graphite n 10 Satisfied: D n 10≥1μm, optionally, 1μm≤D n 10≤3μm. D of artificial graphite n 10 is appropriate, which can make it have a higher gram capacity. In addition, the D n 10 makes its active specific surface area smaller, so there are fewer side reactions between it and the electrolyte, and the cycle expansion of the battery can be further reduced.
[0017] In any embodiment of the first aspect of the present application, the peak intensity I of the D peak of the artificial graphite D The peak intensity of the G peak is G Between: I D / I G ≤0.25, optionally, 0.1≤I D / I G ≤0.2. The I of the artificial graphite of this application D / I G It is smaller, which can be considered that its surface stability is higher, thereby further reducing the volume expansion of the secondary battery during the cycle process.
[0018] In any embodiment of the first aspect of the present application, the artificial graphite includes secondary particles formed by aggregation of primary particles; the number of the secondary particles in the artificial graphite accounts for ≥60%, and can be 70% to 90%. The artificial graphite itself has a low degree of orientation, thereby reducing the cycle expansion of the battery.
[0019] In any embodiment of the first aspect of the present application, the gram capacity of the artificial graphite is 350mAh / g to 359mAh / g; optionally 352mAh / g to 355mAh / g. Artificial graphite has a high gram capacity and a high structural stability. It is not easy to disintegrate in the rolling process of preparing the negative electrode sheet, so that the cohesion between the particles in the sheet is high, thereby reducing the cycle expansion of the sheet and the battery.
[0020] The second aspect of the present application provides a device, which includes the secondary battery according to the first aspect of the present application. The device of the present application includes the secondary battery provided by the present application, and thus has at least the same advantages as the secondary battery.
[0021] The third aspect of the present application provides an artificial graphite, wherein the volume average particle size D of the artificial graphite is v 50 is 12 μm to 22 μm, and the artificial graphite satisfies: 12 ≤ D v 50×SSA≤25, where SSA is the specific surface area of the artificial graphite, in m 2 / g; when the compacted density of the artificial graphite is 1.6g / cm 3 ~1.75g / cm 3 When the negative electrode is used, the peak area C of the 004 crystal surface of the artificial graphite 004 The peak area C of the 110 crystal plane 110 Ratio C 004 / C 110 ≤15.
[0022] A fourth aspect of the present application provides a method for preparing artificial graphite, which comprises the following steps:
[0023] (1) crushing the raw coke materials and performing graded treatment;
[0024] (2) shaping the product obtained in step (1);
[0025] (3) granulating the product obtained in step (2);
[0026] (4) graphitizing the product obtained in step (3) to obtain the artificial graphite;
[0027] Wherein, the volume average particle size D of the artificial graphite v 50 is 12 μm to 22 μm, and the artificial graphite satisfies: 12 ≤ D v 50×SSA≤25, where SSA is the specific surface area of the artificial graphite, in m 2 / g; when the compacted density of the artificial graphite is 1.6g / cm 3 ~1.75g / cm 3 When the negative electrode is used, the peak area C of the 004 crystal surface of the artificial graphite 004 The peak area C of the 110 crystal plane 110 The ratio is ≤15.
[0028] In any embodiment of the fourth aspect of the present application, the green coke includes one or more of green petroleum coke, green asphalt coke and metallurgical coke; optionally, the green coke includes green petroleum coke.
[0029] In any embodiment of the fourth aspect of the present application, the green coke is non-needle coke.
[0030] In any embodiment of the fourth aspect of the present application, the volatile matter content of the raw coke is 6% to 12%, and can be optionally 7% to 10%.
[0031] In any embodiment of the fourth aspect of the present application, the sulfur content of the green coke is ≤2%, and can be optionally ≤0.6%.
[0032] In any embodiment of the fourth aspect of the present application, the step (3) is to granulate the product obtained in the step (2) without adding a binder.
[0033] In any embodiment of the fourth aspect of the present application, the step (2) further comprises removing fine powder after shaping; optionally, the particle size distribution D of the granular product after step (2) is reduced by removing fine powder. n 10 is controlled at ≥0.5μm, and can be optionally controlled at 0.5μm~1.5μm.
[0034] In any embodiment of the fourth aspect of the present application, the product obtained in step (3) is graphitized at a temperature of 2900° C. to 3100° C.
[0035] A fifth aspect of the present application provides a method for preparing a secondary battery, which includes the step of preparing a negative electrode plate using the artificial graphite described in the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.
[0037] Figure 1 It is a schematic diagram of a secondary battery provided in an embodiment of the present application.
[0038] Figure 2 It is a schematic diagram of a battery module provided in an embodiment of the present application.
[0039] Figure 3 It is a schematic diagram of a battery pack provided in an embodiment of the present application.
[0040] Figure 4 yes Figure 3 Exploded diagram of .
[0041] Figure 5 It is a schematic diagram of a device provided in an embodiment of the present application.
[0042] Figure 6a-6c This is a SEM (scanning electron microscope) image of the artificial graphite provided in the examples of the present application.
[0043] The reference numerals are described as follows:
[0044] 1. Battery pack;
[0045] 2. Upper box;
[0046] 3. Lower box;
[0047] 4. Battery module;
[0048] 5. Secondary battery. DETAILED DESCRIPTION
[0049] In order to make the invention purpose, technical scheme and beneficial technical effect of the present application clearer, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the embodiments described in this specification are only for explaining the present application, not for limiting the present application.
[0050] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.
[0051] In the description of this article, it should be noted that, unless otherwise specified, "above" and "below" are inclusive of the number, and "several" in "one or several" means two or more.
[0052] The above-mentioned summary of the invention of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.
[0053] As an economical, practical, clean, and easily controllable and convertible form of energy, electric energy is increasingly being used in various devices. Secondary batteries have become an alternative power source for devices due to their high energy density, portability, no memory effect, and environmental friendliness.
[0054] [Secondary battery]
[0055] Therefore, in a first aspect of the present application, a secondary battery is provided.
[0056] Secondary batteries include positive electrode sheets, negative electrode sheets, and electrolytes. During the battery charging and discharging process, active ions are embedded and extracted back and forth between the positive electrode sheets and the negative electrode sheets. The electrolyte plays the role of conducting ions between the positive electrode sheets and the negative electrode sheets.
[0057] [Negative electrode]
[0058] The negative electrode sheet includes a negative electrode current collector and a negative electrode film disposed on at least one surface of the negative electrode current collector. As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film is laminated on any one or both of the two opposite surfaces of the negative electrode current collector.
[0059] The negative electrode current collector may be made of a material with good electrical conductivity and mechanical strength to perform the functions of conducting and collecting current. In some embodiments, the negative electrode current collector may be made of copper foil.
[0060] The negative electrode membrane includes a negative electrode active material, and the negative electrode active material includes artificial graphite.
[0061] The inventors have done a lot of research and provide an artificial graphite with low expansion performance. The volume average particle size D of the artificial graphite v 50 is 12 μm to 22 μm, and the artificial graphite satisfies: 12 ≤ D v 50×SSA≤25, where SSA is the specific surface area of artificial graphite, in m 2 / g; the compaction density of the negative electrode is 1.6g / cm 3 ~1.75g / cm 3 , the OI value of the negative electrode plate is ≤15, wherein the OI value of the negative electrode plate = C 004 / C 110 , C 004 is the peak area of the diffraction peak of the 004 crystal plane of the artificial graphite in the negative electrode plate, C 110 is the peak area of the diffraction peak of the artificial graphite 110 crystal plane in the negative electrode plate. The peak area of the diffraction peak can be obtained by X-ray diffraction spectrum testing.
[0062] In this application, D v 50×SSA only involves numerical calculations. For example, the D of artificial graphite v 50 is 16.2μm, SSA is 1.15m 2 / g, then the D of artificial graphite v 50×SSA=16.2×1.15≈18.6.
[0063] The inventors of the present application have found that when the volume average particle size D of the artificial graphite v 50 is appropriate, and its D v When the specific surface area SSA and the specific surface area 50 meet a certain relationship, it can make itself have a higher surface stability, reduce the side reaction between it and the electrolyte, and reduce the gas production. At the same time, artificial graphite also meets the compaction density of the negative electrode sheet of 1.6g / cm 3 ~1.75g / cm 3When the ratio of the peak area of the 004 crystal plane of the artificial graphite to the peak area of the 110 crystal plane is within a specific range, the directional selectivity of the artificial graphite in the lithium insertion process is significantly reduced, and the lithium insertion expansion can be dispersed in all directions, thereby reducing the volume expansion of the negative electrode sheet and the secondary battery in the cycle process. Under the combined effect of the above conditions, the cyclic expansion of the artificial graphite is greatly reduced. Therefore, the cyclic expansion of the negative electrode sheet and the secondary battery using the artificial graphite is also significantly reduced.
[0064] The volume increase of the secondary battery during the cycle is small, which is conducive to maintaining a high energy density. In particular, the secondary battery with low cycle expansion can maintain an internal structure suitable for electrolyte infiltration during the cycle, so that the electrolyte can fully infiltrate the battery cell, thereby improving the cycle life of the secondary battery. At the same time, the secondary battery with low cycle expansion can also reduce the internal stress of the battery cell and reduce the deformation of the battery cell under the action of internal stress, so that the safety performance of the secondary battery is also effectively improved. The safety performance of the device using the secondary battery can also be improved.
[0065] In some embodiments, the compaction density of the negative electrode sheet is 1.6 g / cm 3 ~1.75g / cm 3 When the OI value of the negative electrode sheet is ≤15, ≤13, ≤12, or ≤11.5, the OI value of the negative electrode sheet is smaller, and the directional selectivity of the artificial graphite in the lithium insertion process is smaller, and the lithium insertion expansion can be dispersed in all directions, thereby reducing the cycle expansion of the sheet and the battery. Furthermore, the compaction density of the negative electrode sheet is 1.6 g / cm 3 ~1.75g / cm 3 When the OI value of the negative electrode plate can be ≥6, ≥7, ≥8, ≥8.5. In this way, the artificial graphite in the negative electrode plate can have a higher bonding force with the negative electrode current collector, thereby further reducing the cycle expansion of the plate and the battery.
[0066] Optionally, when the compaction density of the negative electrode sheet is 1.6 g / cm 3 ~1.75g / cm 3 When the OI value of the negative electrode is 8-12.
[0067] The compaction density of the negative electrode plate is relatively high, which can enable the secondary battery to obtain a higher energy density, thereby improving the endurance of the device. In some embodiments, the compaction density of the negative electrode plate can be selected to be 1.6 g / cm 3 ~1.7g / cm 3 ; 1.62g / cm2 is optional 3 ~1.68g / cm 3This enables the negative electrode plate to have a high compaction density and a porosity suitable for sufficient infiltration of the electrolyte. Therefore, the capacity of the battery can be more effectively utilized, and the battery can obtain better dynamic performance.
[0068] In some embodiments, the D of the artificial graphite v The value of 50×SSA can be ≥12, ≥13, ≥14, ≥15, ≥16; and can be ≤25, ≤23, ≤22, ≤21, ≤20, ≤18. Optionally, 15≤D v 50×SSA≤22. More preferably, 16≤D v 50×SSA≤21. With appropriate D v The 50×SSA value can further improve the surface stability of artificial graphite.
[0069] In some embodiments, the specific surface area SSA of the artificial graphite may be 0.5 m 2 / g~2.0m 2 / g. For example, the specific surface area SSA of artificial graphite can be 0.5m 2 / g or more, 0.7m 2 / g or more, 0.8m 2 / g or more, 1m 2 / g or more; and can be 2.0m 2 / g or less, 1.8m 2 / g or less, 1.5m 2 / g or less, 1.3m 2 / g or less. Optionally, the BET specific surface area SSA of the artificial graphite is 0.8 m 2 / g~1.5m 2 / g.
[0070] Artificial graphite has an appropriate specific surface area, which can reduce the side reactions of the electrolyte on its surface and reduce the gas production, thereby reducing the volume expansion of the secondary battery during the cycle. At the same time, the artificial graphite can have a high electrochemical reaction activity, so that the secondary battery has a high dynamic performance, which is conducive to meeting the power requirements of the device. In addition, the appropriate specific surface area can also make the artificial graphite have a strong bonding force with the binder, thereby improving the cohesion and bonding force of the pole piece, thereby further reducing the cycle expansion of the secondary battery.
[0071] In some embodiments, the particle size D of the artificial graphite v 50 can be 12 μm to 20 μm. For example, the D v 50 can be 13μm to 18μm, and can be optionally 15μm to 18μm.
[0072] D of artificial graphite v50 is suitable for making it have higher active ion and electron transport performance, and can also reduce the side reaction of the electrolyte at the negative electrode. v 50% artificial graphite is also beneficial to improve its own powder compaction density. The use of this artificial graphite can make the compaction density of the electrode higher, thereby improving the energy density of the battery.
[0073] In some embodiments, the particle size D of the artificial graphite v 10≥6μm. For example, the D of artificial graphite v 10 can be ≥6μm, ≥6.5μm, ≥7μm, ≥7.5μm. The active specific surface area of the artificial graphite is small, which can further reduce the side reaction energy in the secondary battery. Furthermore, the D v 10 can be ≤11μm, ≤10.5μm, ≤10μm, ≤9.5μm, ≤9μm. This is conducive to obtaining a higher compaction density for the pole piece. Optionally, 6.5μm≤D v 10≤10.5μm.
[0074] Definition of artificial graphite particle size span Span = (D v 90-D v 10) / D v 50. In some embodiments, the particle size span of the artificial graphite may be 1.1 to 1.8, and may be 1.2 to 1.5.
[0075] If the particle size span of artificial graphite is appropriate, it contains an appropriate amount of larger particles and smaller particles, which can improve the stacking performance between artificial graphite, and the negative electrode plate using it has an appropriate porosity. At the same time, the artificial graphite can also have an appropriate active specific surface area, so that it has both high electrochemical reaction activity and high surface stability, so that the electrolyte side reaction on the surface of the artificial graphite is less, thereby greatly reducing the electrolyte consumption caused by side reactions and the increase in SEI (solid electrolyte interphase) film thickness on the material surface. In this way, the low cycle expansion performance of the battery is further improved.
[0076] In addition, the appropriate particle size span can also make the artificial graphite have a higher tap density and powder compaction density. Therefore, the compaction density of the pole piece using this artificial graphite is also relatively high, thereby improving the energy density of the battery.
[0077] In some optional embodiments, the artificial graphite may also optionally satisfy the D v 50 is 12μm~22μm, D v 10≥6μm, and (D v 90-D v 10) / Dv 50 is 1.1 to 1.8. The artificial graphite has a good particle matching, which can obtain a higher packing density, thereby increasing the compaction density of the artificial graphite powder, which is beneficial to increasing the energy density of the battery. In addition, the artificial graphite has a good particle matching effect, which can make the negative electrode plate have higher liquid phase ion transmission performance and solid phase ion transmission performance, thereby ensuring that the battery has good dynamic performance.
[0078] The applicant has found that artificial graphite with an appropriate graphitization degree G has a higher gram capacity and also has a higher bulk structure stability. In some embodiments, the graphitization degree G of the artificial graphite is 90% to 95%, optionally 92% to 95%, and more optionally 92% to 94%.
[0079] The graphitization degree of artificial graphite is within the above range, which can make it have a higher powder compaction density and gram capacity. In particular, the graphitization degree G within the above range can also make the artificial graphite less likely to be co-embedded with solvent during the battery cycle, so that the graphite layer is less likely to peel off, thereby reducing the cycle expansion of the pole piece and the battery. At the same time, the structural stability of the artificial graphite is relatively high, and it is not easy to disintegrate in the rolling process of preparing the negative pole piece, so the cohesion between the particles in the pole piece is relatively high, thereby reducing the expansion of the pole piece and the battery during the cycle.
[0080] In some embodiments, the tap density of the artificial graphite may be 0.85 g / cm 3 ~1.35g / cm 3 , optional 0.95g / cm 3 ~1.15g / cm 3 .
[0081] In some embodiments, the powder compaction density of artificial graphite under a pressure of 2000 kg is 1.65 g / cm 3 ~1.85g / cm 3 , optional 1.68g / cm 3 ~1.83g / cm 3 .
[0082] Artificial graphite has a higher powder compaction density under a pressure of 2000kg. The negative electrode sheet using the artificial graphite can have a higher compaction density, thereby making the battery have a higher energy density.
[0083] In some optional embodiments, the number particle size distribution D of artificial graphite n 10≥1μm. For example, D n 10 can be ≥1.2μm, ≥1.3μm, ≥1.5μm. D of artificial graphite n10 is appropriate, which can make it have a higher gram capacity. In addition, the D n 10 makes its active specific surface area smaller, so there are fewer side reactions between it and the electrolyte, and the cycle expansion of the battery can be further reduced.
[0084] Furthermore, the D of artificial graphite n 10≤4μm. For example, D n 10≤4μm, ≤3μm, ≤2.5μm. In artificial graphite containing a proper amount of smaller particles, the smaller particles can fill the pores between larger particles, so that the artificial graphite can also have a higher tap density and powder compaction density, so that the negative electrode plate using it can obtain a higher plate compaction density, thereby further improving the energy density of the battery. Optionally, 1μm≤D n 10≤3μm.
[0085] The D peak and the G peak are Raman characteristic peaks of graphite materials. The D peak and the G peak of artificial graphite can be measured using a laser Raman spectrometer, such as the Advantage 785TM Raman spectrometer. In the Raman spectrum of the artificial graphite of the present application measured by a Raman spectrometer, the D peak is at 1300 cm -1 Up to 1400cm -1 In the range, the G peak is at 1580cm -1 Up to 1620cm -1 Within the range. D / I G The peak intensity I of the D peak is D The peak intensity of the G peak is G Ratio.
[0086] In some optional embodiments, the artificial graphite D / I G ≤0.25. For example, the I D / I G It can be ≤0.23, ≤0.2, ≤0.18, ≤0.16, ≤0.15. The I of the artificial graphite of the present application D / I G The smaller the surface stability, the higher the surface stability, which can further reduce the volume expansion of the secondary battery during the cycle. D / I G It can be ≥0.05, ≥0.08, ≥0.1, ≥0.12. This can make the artificial graphite have a higher electrochemical reaction activity and meet the requirements of battery kinetic performance. Optionally, 0.1≤I D / I G ≤0.2.
[0087] In some embodiments, artificial graphite includes secondary particles formed by aggregation of primary particles, which can make the artificial graphite itself less oriented, thereby reducing the cycle expansion of the battery.
[0088] In some embodiments, the secondary particles may have a shape of one or more of a block, a sphere, and a quasi-spherical shape. The quasi-spherical shape may be, for example, an ellipsoid, a quasi-ellipsoid, or a nearly spherical structure. Figure 6a-6c is a SEM picture of the particle morphology of artificial graphite as an example.
[0089] In some optional embodiments, the number of secondary particles in the artificial graphite accounts for ≥60%, further ≥65%, ≥70%, ≥75%, ≥80%. The OI value of the negative electrode sheet using the artificial graphite is small, so the cyclic expansion of the negative electrode sheet and the battery can be reduced. Furthermore, the number of secondary particles in the artificial graphite accounts for ≤95%, ≤90%, ≤85%. Artificial graphite contains an appropriate amount of primary particles, which can improve its tap density and powder compaction density. Optionally, the number of secondary particles in the artificial graphite accounts for 70% to 90%.
[0090] In some optional embodiments, the gram capacity of the artificial graphite of the present application is 350mAh / g to 359mAh / g, for example, 350mAh / g to 357mAh / g, and another example is 352mAh / g to 355mAh / g. The artificial graphite of the present application has a high gram capacity and a high structural stability. It is not easy to disintegrate in the rolling process of preparing the negative electrode sheet, so that the cohesion between the particles in the electrode sheet is high, thereby reducing the cycle expansion of the electrode sheet and the battery.
[0091] In some embodiments, the negative electrode film may also optionally include other negative electrode active materials that can be used for the negative electrode of a secondary battery. The other negative electrode active materials may be one or more of other graphite materials (such as other artificial graphite, natural graphite), mesophase microcarbon beads (abbreviated as MCMB), hard carbon, soft carbon, silicon-based materials, and tin-based materials.
[0092] In some embodiments, the negative electrode film further includes a binder. As an example, the binder can be selected from one or more of polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0093] In some embodiments, the negative electrode membrane may further include a thickener. As an example, the thickener may be sodium carboxymethylcellulose (CMC-Na).
[0094] In some embodiments, the negative electrode film may further include a conductive agent. As an example, the conductive agent for the negative electrode film may be selected from one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0095] In this application, the D of the artificial graphite n 10. D v 10. D v 50. D v 90 can be measured with reference to standard GB / T19077.1-2016 using a laser particle size analyzer (such as Malvern Master Size 3000).
[0096] Among them, D n 10. D v 10. D v 50. D v The physical definition of 90 is as follows:
[0097] D n 10: The particle size corresponding to when the cumulative number distribution percentage of the artificial graphite reaches 10%;
[0098] D v 10: The particle size corresponding to the cumulative volume distribution percentage of the artificial graphite reaching 10%;
[0099] D v 50: the particle size corresponding to when the cumulative volume distribution percentage of the artificial graphite reaches 50%;
[0100] D v 90: the particle size corresponding to when the cumulative volume distribution percentage of the artificial graphite reaches 90%.
[0101] The specific surface area SSA of the artificial graphite can be tested by methods known in the art. For example, it can be tested by nitrogen adsorption specific surface area analysis test method according to GB / T 19587-2017, and calculated by BET (Brunauer Emmett Teller) method, wherein the nitrogen adsorption specific surface area analysis test can be performed by Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA.
[0102] In the OI value test of the negative electrode, the X-ray diffraction analysis can refer to the standard JISK 0131-1996 and use an X-ray diffractometer (such as Bruker D8 Discover X-ray diffractometer) for testing. In the X-ray diffraction analysis test, a copper target can be used as the anode target, and a Ni filter with a thickness of 0.02 mm can be used to filter the CuK β, CuK α The ray is the radiation source, and the wavelength of the ray is (Take K α1 and K α2 The weighted average value of the scanning 2θ angle range is 20° to 80°, and the scanning rate is 4° / min. In the present application, specifically, the OI value test method of the negative electrode plate is: the prepared negative electrode plate is directly placed in an X-ray diffractometer, and the peak area C of the 004 crystal plane diffraction peak of the negative electrode active material in the negative electrode plate is obtained by X-ray diffraction analysis. 004 And the peak area C of the 110 crystal plane diffraction peak 110 , OI value of negative electrode = C 004 / C 110 .
[0103] The 2θ angle corresponding to the 004 crystal plane of artificial graphite is 53.5° to 55.5° (eg, 54.5°); the 2θ angle corresponding to the 110 crystal plane of artificial graphite is 76.5° to 78.5° (eg, 77.5°).
[0104] The morphology of the artificial graphite can be tested by methods known in the art. For example, the artificial graphite is adhered to a conductive adhesive, and the morphology of the particles is tested using a scanning electron microscope & energy dispersive spectrometer (such as Sigma 300). The test can refer to JY / T010-1996.
[0105] The secondary particle ratio of the artificial graphite can be tested by a prescribed method. For example, the artificial graphite is glued to a conductive adhesive, and the morphology of the particles is tested using a scanning electron microscope & energy spectrometer (such as sigma300). The test can refer to JY / T010-1996. The magnification is 500 times, and the number of secondary particles and the total number of particles are counted. The secondary particle ratio is the ratio of the number of secondary particles to the total number of particles.
[0106] The tap density of the artificial graphite can be tested by methods known in the art, for example, by referring to the standard GB / T5162-2006 and using a powder tap density tester (such as Dandong Better BT-301).
[0107] The compaction density of the artificial graphite powder can be tested by methods known in the art. For example, referring to GB / T24533-2009, an electronic pressure tester (such as UTM7305) can be used for testing: a certain amount of powder is placed on a special compaction mold, different pressures are set, the thickness of the powder under different pressures can be read on the device, and the compaction density under different pressures can be calculated.
[0108] The graphitization degree of the artificial graphite can be tested by methods known in the art. For example, the graphitization degree can be tested using an X-ray diffractometer (such as Bruker D8 Discover). The test can refer to JIS K 0131-1996 and JB / T4220-2011, and the d 002 The size of the G is then calculated according to the formula G = (0.344-d 002 ) / (0.344-0.3354) to calculate the graphitization degree, where d 002 It is the interlayer spacing in the crystal structure of artificial graphite expressed in nanometers.
[0109] [Positive electrode]
[0110] The positive electrode sheet includes a positive electrode current collector and a positive electrode film disposed on at least one surface of the positive electrode current collector and including a positive electrode active material. As an example, the positive electrode current collector has two surfaces opposite to each other in its own thickness direction, and the positive electrode film is laminated on any one or both of the two opposite surfaces of the positive electrode current collector.
[0111] The positive electrode current collector may be made of a material having good electrical conductivity and mechanical strength. In some embodiments, the positive electrode current collector may be aluminum foil.
[0112] The present application does not impose any specific restrictions on the specific type of positive electrode active material. Materials known in the art that can be used for secondary battery positive electrodes can be used, and those skilled in the art can make a selection based on actual needs.
[0113] In some embodiments, the secondary battery may be a lithium ion secondary battery. The positive electrode active material may be selected from lithium transition metal oxides and modified materials thereof, and the modified material may be a lithium transition metal oxide that is doped and / or coated. For example, the lithium transition metal oxide may be selected from one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium phosphates having an olivine structure.
[0114] As an example, the positive electrode active material of the secondary battery can be selected from LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 One or more of O2, LiFePO4 (LFP) and LiMnPO4.
[0115] In some embodiments, the positive electrode membrane may also optionally include a binder. There is no specific limitation on the type of the binder, and those skilled in the art may select it according to actual needs. As an example, the binder for the positive electrode membrane may include one or more of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).
[0116] In some embodiments, the positive electrode film may further include a conductive agent. There is no specific limitation on the type of the conductive agent, and those skilled in the art may select the conductive agent according to actual needs. As an example, the conductive agent used for the positive electrode film may include one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0117] [Electrolytes]
[0118] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolyte).
[0119] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0120] In some embodiments, the electrolyte salt can be selected from one or more of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalatoborate), LiBOB (lithium dioxalatoborate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorooxalatophosphate) and LiTFOP (lithium tetrafluorooxalatophosphate).
[0121] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0122] In some embodiments, the electrolyte may optionally include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.
[0123] [Isolation film]
[0124] Secondary batteries using electrolytes and some secondary batteries using solid electrolytes also include a separator. The separator is arranged between the positive electrode plate and the negative electrode plate to play an isolating role. The present application has no particular restrictions on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected. In some embodiments, the material of the separator can be selected from one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer can be the same or different.
[0125] [Outer packaging]
[0126] In some embodiments, the secondary battery may include an outer package for packaging the positive electrode sheet, the negative electrode sheet and the electrolyte. As an example, the positive electrode sheet, the negative electrode sheet and the separator may be laminated or wound to form a laminated structure battery cell or a wound structure battery cell, and the battery cell is packaged in the outer package; the electrolyte may be an electrolyte, and the electrolyte is infiltrated in the battery cell. The number of batteries in the secondary battery may be one or more, which can be adjusted according to demand.
[0127] In some embodiments, the outer packaging of the secondary battery may be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene PP, polybutylene terephthalate PBT, polybutylene succinate PBS, etc. The outer packaging of the secondary battery may also be a hard shell, such as an aluminum shell, etc.
[0128] [Preparation method]
[0129] The preparation of a secondary battery may include the steps of assembling a negative electrode sheet, a positive electrode sheet and an electrolyte to form a secondary battery. In some embodiments, the positive electrode sheet, the separator and the negative electrode sheet may be wound or stacked in sequence, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, thereby obtaining a battery cell; the battery cell is placed in an outer package, and the electrolyte is injected and sealed to obtain a secondary battery.
[0130] In some embodiments, the preparation of the secondary battery may further include the step of preparing a positive electrode sheet. As an example, the positive electrode active material, the conductive agent and the binder may be dispersed in a solvent (e.g., N-methylpyrrolidone, referred to as NMP) to form a uniform positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, a positive electrode sheet is obtained.
[0131] In some embodiments, the preparation of a secondary battery includes the step of preparing a negative electrode sheet using any one or more of the artificial graphites of the present application.
[0132] In some embodiments, the step of preparing a negative electrode sheet using any one or several artificial graphites of the present application may include: dispersing a negative electrode active material including any one or several artificial graphites of the present application, a binder, and an optional thickener and a conductive agent in a solvent, the solvent may be deionized water, to form a uniform negative electrode slurry; coating the negative electrode slurry on a negative electrode collector, and obtaining a negative electrode sheet after drying, cold pressing and other processes.
[0133] Next, the present application also provides a method for preparing artificial graphite, by which any of the above-mentioned artificial graphites can be prepared.
[0134] The present invention provides a method for preparing artificial graphite, comprising the following steps:
[0135] S10, crushing the raw coke materials and performing graded treatment.
[0136] S20, shaping the product obtained in step S10.
[0137] S30, granulating the product obtained in step S20.
[0138] S40, graphitizing the product obtained in step S30 to obtain the artificial graphite.
[0139] In the above preparation method, in step S10, the raw coke material can be selected from one or more of green petroleum coke, green asphalt coke and metallurgical coke, and can optionally include green petroleum coke.
[0140] Optionally, the green coke is non-needle coke. The non-needle coke can be selected from one or more of non-needle green petroleum coke, non-needle green asphalt coke and non-needle metallurgical coke. Optionally, the non-needle coke includes non-needle green petroleum coke.
[0141] In some embodiments, in step S10, optionally, the volatile content of the green coke is 6% to 12% (weight percentage). For example, the volatile content of the green coke powder can be more than 6%, more than 6.5%, more than 7%, more than 7.5%; and can be less than 12%, less than 11%, less than 10%, less than 9%. Optionally, the volatile content of the green coke is 7% to 10%.
[0142] The coke raw material has an appropriate volatile content, which can make it have high self-adhesiveness during the granulation process in step S20, improve the bonding strength between primary particles in the artificial graphite, and make the artificial graphite have high structural strength. At the same time, the coke raw material is also conducive to forming a dense structure of the artificial graphite, further improving the structural strength of the artificial graphite.
[0143] The volatile matter content of green coke can be measured by methods known in the art, for example, by referring to SH / T 0026-1990.
[0144] In some embodiments, the sulfur content of the raw coke may be ≤2%, ≤1.5%, ≤1%, ≤0.6%. The raw coke has a lower sulfur content, which can prevent the increase in the specific surface area of the graphite material caused by the escape of more sulfur components in the subsequent process. This is conducive to making the specific surface area of the artificial graphite meet the requirements mentioned above. Optionally, the sulfur content of the raw coke material is ≤0.6%.
[0145] The sulfur content of green coke can be tested by methods known in the art, for example, by referring to GB / T 2286-2008.
[0146] In step S10, the raw coke material can be crushed using equipment and methods known in the art, such as a jet mill, a mechanical mill or a roller mill. The crushing process often produces a large number of undersized particles, and sometimes there are oversized particles. Therefore, after crushing, classification treatment can be performed as required to remove the undersized particles and oversized particles in the crushed powder. After classification treatment, a particle product with a good particle size distribution can be obtained to facilitate subsequent shaping and granulation processes. Classification treatment can be performed using equipment and methods known in the art, such as a grading screen, a gravity classifier, a centrifugal classifier, etc.
[0147] The particle size distribution of the granular product obtained by adjusting step S10 is as follows: v 10. D v 50 and / or D v90 Within an appropriate range, the granulation degree in the subsequent granulation step can be improved, so that the artificial graphite itself has a higher isotropy and a higher gram capacity.
[0148] In step S20, the edges and corners of the particle product obtained in step S10 are polished by shaping, so as to facilitate the subsequent granulation process and make the secondary particles in the obtained artificial graphite have higher stability.
[0149] In step S20, the granular product obtained in step S10 may be shaped by using equipment and methods known in the art, such as a shaping machine or other shaping equipment.
[0150] In some embodiments, step 20 further includes removing fine powder after shaping. By removing fine powder after shaping, the D of the granular product after shaping can be adjusted. n 10 is within an appropriate range so that the D of the obtained artificial graphite n 10 is within the desired range. In some embodiments, in step 20, the D of the obtained granular product can be n 10 is controlled at ≥0.5μm, and can be optionally controlled at 0.5μm~1.5μm.
[0151] The fine powder can be removed by using equipment and methods known in the art, such as a grading screen, a gravity classifier, a centrifugal classifier, and the like.
[0152] In step S30, the granular product obtained in step S20 is granulated so that the independently dispersed primary particles are aggregated to form secondary particles, thereby significantly improving the isotropy of the artificial graphite and reducing the OI of the negative electrode. During the granulation process, the amount of the binder does not exceed 5% of the total weight of the raw coke material (that is, the amount of the binder is less than or equal to 5% of the total weight of the raw coke material). Optionally, the product obtained in step S20 is granulated without adding a binder (that is, the amount of the binder accounts for 0% of the total weight of the raw coke material). For example, when the volatile content of the raw coke is above 7%, the step S30 can granulate the granular product obtained in step 20 without adding a binder.
[0153] Granulation under the condition of reducing or not having a binder can further improve the gram capacity of artificial graphite. In particular, under the condition of reducing or not having a binder, granulation using the self-adhesiveness of raw coke can improve the overall structural strength of artificial graphite particles, thereby further reducing the cycle expansion of the battery. However, the content of volatile matter should not be too large, otherwise it will significantly reduce the gram capacity of the negative electrode active material and affect its processing performance during subsequent use.
[0154] In step S30, granulation can be performed using equipment known in the art, such as a granulator. A granulator generally includes a stirred reactor and a module for controlling the temperature of the reactor. By regulating the stirring speed, heating rate, granulation temperature, cooling rate, etc. during the granulation process, it is beneficial to improve the structural strength and isotropy of the obtained artificial graphite, and to make the C 004 / C 110 Meet the needs.
[0155] Furthermore, by adjusting the above process conditions, the volume average particle size D of the granulated product can be adjusted. v 50 is within the required range, or the D of the granulated product is v 10. D v 50 and D v 90 are all within the required range.
[0156] By adjusting the particle size distribution of step S10 and / or S30, the D of the artificial graphite finally prepared can be v 50. D v 10. D v 90 and / or (D v 90-D v 10) / D v 50 is within the required range.
[0157] In step S40, the granulated product obtained in step S30 is graphitized to obtain artificial graphite with an appropriate degree of graphitization. In some embodiments, the temperature of the graphitization treatment in step S40 can be 2800° C. to 3200° C., and can be optionally 2900° C. to 3100° C. The artificial graphite prepared at an appropriate graphitization temperature can obtain an appropriate degree of graphitization, thereby obtaining a higher structural stability and gram capacity.
[0158] In step S40, graphitization can be performed using equipment known in the art, such as a graphitization furnace, and further, an Acheson graphitization furnace. After the graphitization treatment is completed, a small amount of oversized particles formed by agglomeration of the granulated product during the high-temperature graphitization process can be removed by screening. This can prevent oversized particles from affecting material processing properties, such as slurry stability, coating properties, etc.
[0159] In some embodiments, after step S40, step S50 may be further included: mixing the artificial graphite obtained in step S40 with an organic carbon source, and then heating the mixture at a temperature of 850° C. to 1250° C. to obtain artificial graphite having an amorphous carbon coating layer. The organic carbon source may be selected from one or more of phenolic resin, asphalt, furfural resin, and epoxy resin, and may be asphalt.
[0160] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.
[0161] In some embodiments, secondary batteries may be assembled into a battery module. The battery module may contain multiple secondary batteries, and the specific number may be adjusted according to the application and capacity of the battery module.
[0162] Figure 2 4 is an example of a battery module. Figure 2 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0163] Optionally, the battery module 4 may further include a housing having a housing space, and the plurality of secondary batteries 5 are housed in the housing space.
[0164] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0165] Figure 3 and Figure 4 1 is a battery pack 1 as an example. Figure 3 and Figure 4 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0166] [Device]
[0167] In a second aspect of the present application, a device is provided, the device comprising the secondary battery of the first aspect of the present application, the secondary battery providing power for the device. The device may be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0168] The device can select a secondary battery, a battery module or a battery pack according to its usage requirements.
[0169] Figure 5The device is used as an example. The device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.
[0170] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0171] Example
[0172] The following examples more specifically describe the disclosure of the present application, which are intended for illustrative purposes only, as it will be apparent to those skilled in the art that various modifications and variations are possible within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0173] test
[0174] (1) Gram capacity test of artificial graphite
[0175] The prepared artificial graphite, conductive agent Super P, binder (PVDF) and solvent NMP (N-methylpyrrolidone) are mixed uniformly in a mass ratio of 91.6:1.8:6.6 to prepare a slurry; the prepared slurry is coated on a copper foil current collector, dried in an oven and set aside; a metal lithium sheet is used as a counter electrode; a polyethylene (PE) film is used as an isolation membrane; ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1, and then LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte, wherein the concentration of LiPF6 is 1 mol / L; the above parts are assembled into a CR2430 button battery in an argon-protected glove box.
[0176] After the button cell was left to stand for 12 hours, it was discharged at a constant current of 0.05C to 0.005V, left to stand for 10 minutes, and then discharged at a constant current of 50μA to 0.005V, left to stand for 10 minutes, and then discharged at a constant current of 10μA to 0.005V; then it was charged at a constant current of 0.1C to 2V, and the charging capacity was recorded. The ratio of the charging capacity to the mass of the artificial graphite is the gram capacity of the prepared artificial graphite.
[0177] (2) Cyclic expansion rate test of negative electrode
[0178] The thickness of the negative electrode after cold pressing is recorded as H0. The cold pressed negative electrode, positive electrode, separator and electrolyte are made into a secondary battery. At 25°C, the secondary battery is cycled at 100% DOD (100% depth of discharge, that is, fully charged and then fully discharged) 1C / 1C in a Xinwei charger and discharger. The discharge capacity (i.e. initial capacity) of the first cycle is recorded as 100%, and the cycle stops when the cycle capacity retention rate is 80% of the initial capacity. Then charge the secondary battery to 100% SOC (State of Charge), disassemble the secondary battery and test the thickness of the corresponding negative electrode, which is recorded as H1. The cycle expansion rate of the negative electrode is: (H1 / H0-1)×100%.
[0179] (3) Battery dynamic performance test
[0180] At 25°C, the batteries prepared in the examples and comparative examples were fully charged at x C and fully discharged at 1 C for 10 times, and then the batteries were fully charged at x C again, and then the negative electrode plates were disassembled and the lithium deposition on the surface of the negative electrode plates was observed. If no lithium deposition was observed on the negative electrode surface, the charging rate x C was increased by 0.1 C as a gradient and tested again until lithium deposition was observed on the negative electrode surface, and the test was stopped. The charging rate (x-0.1) C at this time was the maximum charging rate of the battery.
[0181] (4) Secondary battery energy density test
[0182] At 25°C, the secondary batteries prepared in the embodiments and comparative examples were subjected to charge and discharge tests at 1 / 3C-1 / 3C (the test instrument can be a Xinwei tester), with a voltage range of 2.8V to 4.3V. The energy released in the first cycle of the battery was recorded and then divided by the weight of the battery to obtain the weight energy density of the battery, in Wh / kg.
[0183] Example 1
[0184] Preparation of artificial graphite
[0185] 1) Raw material crushing: Use a mechanical mill or a roller mill to crush the raw material non-needle-shaped green petroleum coke. The non-needle-shaped green petroleum coke has a volatile matter content of 12% and a sulfur content of 0.6%. After crushing, a classification process is performed to adjust the particle size distribution of the obtained granular product.
[0186] 2) Shaping: Shaping the granular products obtained after crushing.
[0187] 3) Granulation: The granular product obtained after shaping is added into the reaction kettle of the granulator, and the raw coke powder is granulated without adding a binder.
[0188] 4) Graphitization: The granulated product is added into a graphitization furnace and heated to 3000°C for ultra-high temperature graphitization to obtain artificial graphite.
[0189] Preparation of negative electrode
[0190] The artificial graphite, conductive agent (Super P), binder (styrene-butadiene rubber emulsion), and thickener (CMC-Na) prepared above were fully stirred and mixed in a proper amount of deionized water at a mass ratio of 96.2:0.8:1.8:1.2 to form a uniform negative electrode slurry; the negative electrode slurry was coated on the surface of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet was obtained. The compaction density of the negative electrode sheet is 1.65g / cm 3 , surface density is 10.7mg / cm 2 .
[0191] Preparation of positive electrode
[0192] The positive electrode active material LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), conductive agent (Super P), and binder PVDF are fully stirred and mixed in an appropriate amount of NMP at a weight ratio of 96.2:2.7:1.1 to form a uniform positive electrode slurry; the positive electrode slurry is coated on the surface of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained. The compaction density of the positive electrode sheet is 3.45g / cm 3 , surface density is 18.8mg / cm 2 .
[0193] Preparation of electrolyte
[0194] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1, and then LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte, wherein the concentration of LiPF6 is 1 mol / L.
[0195] Isolation film
[0196] Polyethylene (PE) film is used.
[0197] Preparation of secondary batteries
[0198] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, and the battery core is obtained after winding. The battery core is placed in an outer package, and the above-mentioned electrolyte is added. After packaging, standing, forming, aging and other processes, a secondary battery is obtained. The outer package is a hard shell case with a length*width*height=148mm*28.5mm*97.5mm.
[0199] Embodiments 2 to 10
[0200] The preparation method is similar to that of Example 1, except that the preparation parameters of artificial graphite are adjusted to obtain graphite with different D v 50×SSA and OI artificial graphite.
[0201] Comparative Examples 1 to 5
[0202] The preparation method is similar to that of Example 1. The difference from Example 1 is that the preparation parameters of artificial graphite are adjusted to obtain graphite with different D v 50×SSA and OI artificial graphite; and, the raw materials of comparative examples 1 to 4 are calcined needle petroleum coke (i.e., needle-shaped cooked petroleum coke), and comparative example 2 omits the granulation step 3), and the granulation step 3) of comparative examples 1 and 3 adds binder asphalt, and the amount of asphalt accounts for 8% of the total weight of the raw materials; comparative example 4 also includes the step of coating the artificial graphite with asphalt after the graphitization treatment step 4), and carbonizing it in a protective atmosphere at 1050°C.
[0203] Table 1: Artificial graphite preparation parameters of Examples 1 to 10 and Comparative Examples 1 to 5
[0204]
[0205] Table 2: Parameter test results of Examples 1 to 10 and Comparative Examples 1 to 5
[0206]
[0207] In Table 2 and the following tables: Y = D v 50×SSA; Granularity span = (D v 90-D v 10) / D v 50.
[0208] Other parameters of artificial graphite in Table 2: The degree of graphitization of the artificial graphite of Examples 1-10 and Comparative Examples 1-5 is about 92% to 93%; The I D / I G is about 0.16 to 0.18, and the I of the artificial graphite of Comparative Example 4 D / I G It is 0.33.
[0209] Table 3: Performance test results of Examples 1 to 10 and Comparative Examples 1 to 5
[0210] Pole cyclic expansion rate [%] Artificial graphite gram capacity [mAh / g] Dynamic performance Example 1 28.6 351.2 1.5C Example 2 28.9 351.1 1.5C Example 3 29.1 350.8 1.5C Example 4 29.4 350.2 1.6C Example 5 29.6 350.1 1.6C Example 6 28.8 352.0 1.4C Example 7 29.0 351.5 1.4C Example 8 28.9 351.1 1.5C Example 9 29.4 350.7 1.5C Example 10 29.6 348.6 1.6C Comparative Example 1 34.6 350.8 1.4C Comparative Example 2 37.4 350.9 1.5C Comparative Example 3 36.5 350.6 1.4C Comparative Example 4 36.1 347.3 1.7C Comparative Example 5 35.3 346.4 1.6C
[0211] From the comparison between Examples 1-10 and Comparative Examples 1-5, it can be seen that the negative electrode sheet of the secondary battery includes a negative electrode active material, the negative electrode active material includes artificial graphite, and the D v 50 is within an appropriate range, and the D of the artificial graphite v 50 and SSA satisfy an appropriate relationship, and the negative electrode sheet has a compaction density of 1.6 g / cm 3 ~1.75g / cm 3 When the OI value is within an appropriate range, the cycle expansion of the battery can be effectively reduced without affecting the gram capacity of the artificial graphite.
[0212] In Comparative Example 1, the artificial graphite has a higher OI value and poor isotropy. Its expansion during the lithium insertion process cannot be dispersed in all directions, resulting in a larger cyclic expansion rate of the electrode.
[0213] In Comparative Examples 2 and 3, the D v 50×SSA is appropriate, but its D v 50 is larger or smaller, resulting in a higher OI value of the negative electrode sheet, resulting in a larger cycle expansion rate of the negative electrode sheet using it. v 50 is too small to obtain a high pole piece compaction density.
[0214] In Comparative Examples 4 and 5, the D v 50 and the OI values of the negative electrode are within the appropriate range, but their D v A smaller or larger 50×SSA value will cause a larger cycle expansion rate of the negative electrode plate using it, and will also affect its own gram capacity. Moreover, it is difficult to obtain a higher electrode plate compaction density by using the coated artificial graphite in Comparative Example 4.
[0215] Examples 11-15 and Comparative Examples 6-7
[0216] The preparation method is similar to that of Example 4, except that the compaction density of the negative electrode sheet is adjusted.
[0217] Table 4: Parameter test results of Examples 11 to 15 and Comparative Examples 6 to 7
[0218]
[0219] Table 5: Performance test results of Examples 11 to 15 and Comparative Examples 6 to 7
[0220] Pole cyclic expansion rate [%] Battery energy density [Wh / kg] Dynamic performance Embodiment 11 28.1 224.8 1.6C Example 12 28.6 225.0 1.6C Embodiment 13 29.6 225.3 1.5C Embodiment 14 29.9 225.6 1.5C Embodiment 15 30.1 226.3 1.4C Comparative Example 6 27.9 223.6 1.7C Comparative Example 7 30.8 227.1 1.3C
[0221] It can be concluded from Examples 11-15 that when the compaction density of the negative electrode sheet is within the given range, the battery can simultaneously have lower cycle expansion, higher energy density and better kinetic performance.
[0222] The negative electrode sheet of Comparative Example 6 has a lower compaction density, and its corresponding battery energy density is lower.
[0223] The negative electrode sheet of Comparative Example 7 has a higher compaction density, a larger cycle expansion of the battery, and poorer kinetic performance.
[0224] Examples 18-24
[0225] The preparation method is similar to that of Example 4, except that: in step 2) of preparing the artificial graphite, the fine powder is removed after shaping to adjust the D n 10.
[0226] Table 6: Parameter test results of Examples 18 to 24
[0227]
[0228] Other parameters of artificial graphite: The degree of graphitization of the artificial graphite of Examples 18-24 is about 92% to 93%; D / I G It is about 0.16 to 0.18.
[0229] Table 7: Performance test results of Examples 18 to 24
[0230] Pole cyclic expansion rate [%] Artificial graphite gram capacity [mAh / g] Embodiment 18 28.1 353.9 Embodiment 19 28.1 354.1 Embodiment 20 28.6 354.6 Embodiment 21 28.9 355.3 Embodiment 22 28.4 356.2 Embodiment 23 28.7 356.5 Embodiment 24 28.6 356.7
[0231] It can be seen from the comparison between Examples 18-24 and Example 4 that when the artificial graphite also meets its D n 10 When it is within an appropriate range, it can improve the cyclic expansion of the electrode and the battery while increasing the gram capacity of the artificial graphite.
[0232] Examples 25-27
[0233] The preparation method is similar to that of Example 20, except that raw coke with different volatile matter contents is selected.
[0234] Table 8: Artificial graphite preparation parameters of Examples 25-27
[0235]
[0236] Table 9: Parameter test results of Examples 25-27
[0237]
[0238] Other parameters of artificial graphite: The degree of graphitization of the artificial graphite of Examples 25-27 is about 92% to 93%; D / I G It is about 0.16 to 0.18.
[0239] Table 10: Performance test results of Examples 25-27
[0240] Pole cyclic expansion rate [%] Artificial graphite gram capacity [mAh / g] Embodiment 25 28.1 355.3 Embodiment 26 28.2 354.9 Embodiment 27 29.0 354.2
[0241] It can be seen from the results of Examples 25-27 and Example 20 that an appropriate content of volatile matter can improve the structural stability of artificial graphite and further reduce the cyclic expansion of the electrode and the battery; at the same time, it can also make the artificial graphite have a higher gram capacity.
[0242] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. A secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode active material, wherein the negative electrode active material comprises artificial graphite, and the volume average particle size D of the artificial graphite is v 50 is 12μm ~ 22μm, and the artificial graphite satisfies: 12≤D v 50×SSA≤25, where SSA is the specific surface area of the artificial graphite, in m 2 / g; The compaction density of the negative electrode plate is 1.6 g / cm 3 ~ 1.75g / cm 3 ; The OI value of the negative electrode plate is ≤15, wherein the OI value of the negative electrode plate = C 004 / C 110 , C 004 is the peak area of the diffraction peak of the artificial graphite 004 crystal plane in the X-ray diffraction spectrum of the negative electrode plate, C 110 is the peak area of the diffraction peak of the artificial graphite 110 crystal plane in the X-ray diffraction spectrum of the negative electrode plate, The number particle size distribution D of the artificial graphite n 10Satisfy: 1μm≤D n 10≤3μm; The artificial graphite includes secondary particles formed by aggregation of primary particles.
2. The secondary battery according to claim 1, wherein The volume average particle size D of the artificial graphite v 50 is 15μm ~18μm.
3. The secondary battery according to claim 1, wherein The artificial graphite satisfies: 15≤D v 50×SSA≤22.
4. The secondary battery according to claim 3, wherein The artificial graphite satisfies: 16≤D v 50×SSA≤21.
5. The secondary battery according to any one of claims 1 to 4, wherein: The compaction density of the negative electrode plate is 1.6 g / cm 3 ~ 1.7g / cm 3 .
6. The secondary battery according to claim 5, wherein The compaction density of the negative electrode plate is 1.62 g / cm 3 ~1.68g / cm 3 .
7. The secondary battery according to any one of claims 1 to 4, wherein: The OI value of the negative electrode plate is 8 to 12.
8. The secondary battery according to any one of claims 1 to 4, wherein: The volume particle size distribution D of the artificial graphite v 10 ≥ 6 μm; and / or, The particle size span of the artificial graphite (D v 90-D v 10) / D v 50 is 1.1 ~ 1.
8.
9. The secondary battery according to claim 8, wherein The volume particle size distribution D of the artificial graphite v 10: 6.5μm≤D v 10≤10.5μm.
10. The secondary battery according to claim 8, wherein The particle size span (D v 90-D v 10) / D v 50 is 1.2 ~ 1.
5.
11. The secondary battery according to any one of claims 1 to 4, wherein: The degree of graphitization of the artificial graphite is 90% to 95%.
12. The secondary battery according to claim 11, wherein The degree of graphitization of the artificial graphite is 92% to 94%.
13. The secondary battery according to any one of claims 1 to 4, wherein: The tap density of the artificial graphite is 0.85 g / cm 3 ~ 1.35g / cm 3 and / or, The compacted density of the artificial graphite powder under a pressure of 2000 kg is 1.65 g / cm 3 ~ 1.85g / cm 3 .
14. The secondary battery according to claim 13, wherein The tap density of the artificial graphite is 0.95 g / cm 3 ~1.15g / cm 3 .
15. The secondary battery according to claim 13, wherein The compacted density of the artificial graphite powder under a pressure of 2000 kg is 1.68 g / cm 3 ~ 1.83g / cm 3 .
16. The secondary battery according to any one of claims 1 to 4, wherein: The peak intensity I of the D peak of the artificial graphite D The peak intensity of the G peak is G Between: I D / I G ≤0.
25.
17. The secondary battery according to claim 16, wherein The peak intensity I of the D peak of the artificial graphite D The peak intensity of the G peak is G Satisfy between: 0.1≤I D / I G ≤0.
2.
18. The secondary battery according to any one of claims 1 to 4, wherein: The secondary particles account for ≥60% of the artificial graphite.
19. The secondary battery according to claim 18, wherein The secondary particles account for 70% to 90% of the artificial graphite.
20. The secondary battery according to any one of claims 1 to 4, wherein The gram capacity of the artificial graphite is 350mAh / g to 359mAh / g.
21. The secondary battery according to claim 20, wherein The gram capacity of the artificial graphite is 352 mAh / g to 355 mAh / g.
22. An electric device comprising the secondary battery according to any one of claims 1 to 21.
23. An artificial graphite, wherein: The volume average particle size D of the artificial graphite v 50 is 12μm ~ 22μm, and the artificial graphite satisfies: 12≤D v 50×SSA≤25, where SSA is the specific surface area of the artificial graphite, in m 2 / g; when the compacted density of the artificial graphite is 1.6g / cm 3 ~ 1.75g / cm 3 When the negative electrode sheet is in the negative electrode sheet, in the X-ray diffraction spectrum of the negative electrode sheet, the peak area C of the 004 crystal plane diffraction peak of the artificial graphite 004 The peak area C of the diffraction peak of the 110 crystal plane 110 Ratio C 004 / C 110 ≤15, the number particle size distribution D of the artificial graphite n 10Satisfy: 1μm≤D n 10≤3μm; the artificial graphite includes secondary particles formed by aggregation of primary particles.
24. A method for preparing artificial graphite, comprising the following steps: (1) Crushing and classifying the raw coke; (2) shaping the product obtained in step (1); (3) granulating the product obtained in step (2), wherein the amount of binder added in the granulation process does not exceed 5% of the total weight of the raw coke material; (4) graphitizing the product obtained in step (3) at a temperature of 2800° C. to 3200° C. to obtain the artificial graphite; Wherein, the volume average particle size D of the artificial graphite v 50 is 12μm ~ 22μm, and the artificial graphite satisfies: 12≤D v 50×SSA≤25, where SSA is the specific surface area of the artificial graphite, in m 2 / g; when the compacted density of the artificial graphite is 1.6g / cm 3 ~ 1.75g / cm 3 When the negative electrode sheet is in the negative electrode sheet, in the X-ray diffraction spectrum of the negative electrode sheet, the peak area C of the 004 crystal plane diffraction peak of the artificial graphite 004 The peak area C of the diffraction peak of the 110 crystal plane 110 Ratio C 004 / C 110 ≤15, The number particle size distribution D of the artificial graphite n 10Satisfy: 1μm≤D n 10≤3μm; The artificial graphite includes secondary particles formed by aggregation of primary particles.
25. The preparation method according to claim 24, wherein: The green coke includes one or more of green petroleum coke, green asphalt coke and metallurgical coke.
26. The preparation method according to claim 25, wherein: The green coke includes green petroleum coke.
27. The preparation method according to claim 25, wherein: The green coke is non-needle coke.
28. The preparation method according to any one of claims 24 to 27, wherein: The volatile matter content of the raw coke is 6% to 12%; and / or, The sulfur content of the green coke is ≤2%.
29. The preparation method according to claim 28, wherein The volatile matter content of the raw coke is 7% to 10%.
30. The preparation method according to claim 28, wherein the sulfur content of the green coke is ≤0.6%.
31. The preparation method according to any one of claims 24 to 27, wherein: The step (3) is to granulate the product obtained in the step (2) without adding a binder.
32. The preparation method according to any one of claims 24 to 27, wherein: The step (2) also includes removing fine powder after shaping.
33. The preparation method according to any one of claims 24 to 27, wherein: By removing the subdivision, the particle size distribution D of the granular product after step (2) is n 10Controlled at ≥0.5μm.
34. The preparation method according to any one of claims 24 to 27, wherein: By removing the subdivision, the particle size distribution D of the granular product after step (2) is n 10 is controlled at 0.5μm ~ 1.5μm.
35. The preparation method according to any one of claims 24 to 27, wherein: The product obtained in step (3) is graphitized at a temperature of 2900° C. to 3100° C.
36. A method for preparing a secondary battery, comprising the step of preparing a negative electrode plate using the artificial graphite according to claim 23.
Citation Information
Patent Citations
Negative electrode material for lithium secondary battery, manufacturing method of the same, negative electrode for lithium secondary battery using the same, and lithium secondary battery
JP2012023048A
Negative electrode material for nonaqueous secondary battery, and lithium ion secondary battery
JP2017174739A